Effect of spraying fertilizer paper and aqueous extract of licorice in the content of the fruits of two varieties of sweet peppers total Azaúbh solids and vitamin (Baghdad Science Journal, 2006)
Studied the effect of foliar fertilizers Alaongrin results showed that spraying fertilizer Alaongrin and Fertilizers and Ministry of Agriculture and rack licorice extract every three weeks after thirty days from planting seedlings